R. N. Perham at the helm: 1998–2013. (5th November 2013) - Parham, Peter
<x xml:space="preserve">Abstract</x> With this issue of FEBS Journal Richard Perham's fifteen‐year tenure as Editor‐in‐Chief comes to a close. During his time the twentieth century was left behind and in scope and scale the biological sciences expanded in ways resembling the stuff of science fiction. In response, the journal co‐evolved with changes in the science and in the scientific community that the journal serves..<boxed-text content-type="graphic" id="febs12585-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>